DERMATOLOGICAL PREPARATIONS, FORMULATION AND EVALUATION OF VARIOUS SEMI-SOLID DOSAGE FORM - Sharma, Sanjeev; Singh, S. P. (Asian Journal of Pharmaceutical Research and Development, 2014)
There are many dosage forms in present era, which also include dermatological preparations or topical product which are applied over skin part for their desire action Dermatological preparations are manufacture to local action on skin and by pass first pass metabolism. The purpose of this study is preparation, formulation and evaluation of various semi-solid dosage forms like ointment, creams, paste, gels.